2017
DOI: 10.1159/000464442
|View full text |Cite
|
Sign up to set email alerts
|

Two-Thirds of Survey Respondents in Southern Sweden Used Complementary or Alternative Medicine in 2015

Abstract: Background: Research has long suggested that a large and possibly growing number of people use complementary or alternative medicine (CAM). However, in many countries, such as Sweden, national and regional research on CAM use is still very limited. Existing prevalence studies are few and characterized by low comparability. This study aims to contribute towards addressing this knowledge gap. Methods: A web-based survey measured the use of and attitude towards CAM and conventional medicine in the southernmost Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
2
15
3
1
Order By: Relevance
“…It has been adapted for use by investigators in several countries; for example, in France, 43 Sweden, 44 Korea, 45 and Argentina. 46 The I-CAM-Q addresses the use of conventional health care providers, alternative health care providers, and traditional healers, the use of supplements (herbs, vitamins, OTC medicine, home remedies), and the use of self-care practices.…”
Section: Data Collectionmentioning
confidence: 99%
“…It has been adapted for use by investigators in several countries; for example, in France, 43 Sweden, 44 Korea, 45 and Argentina. 46 The I-CAM-Q addresses the use of conventional health care providers, alternative health care providers, and traditional healers, the use of supplements (herbs, vitamins, OTC medicine, home remedies), and the use of self-care practices.…”
Section: Data Collectionmentioning
confidence: 99%
“…The questionnaire was presented in a publication in 2009, with instructions for translation and cultural adaptation [14]. From 2012 to present, the questionnaire has been translated and adapted to many different countries and languages [15][16][17][18][19][20]. The I-CAM-Q instrument has been applied worldwide such as in France [15], Germany [20], Iran [16], Saudi Arabia [21], US [22,23], Argentina [24], Japan [25,26], Taiwan [17], Korea [18], Cambodia [27] and Australia [28].…”
Section: Introductionmentioning
confidence: 99%
“…CAM services were utilized by 27% of the patients, 21% reported use of CAM products, and 28% had used self-help practices [30]. In 2017, Wemrell et al [19] applied the I-CAM-Q instrument when investigating the utilization of CAM in Sweden. The researchers found that 71% of the respondents had used CAM in the past year.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in an international group of CAM researchers, a standardized questionnaire, the International Questionnaire to measure use of Complementary and Alternative Medicine (I-CAM-Q), was developed to reduce questionnaire-related bias and to conduct an international comparison of the utilization of CAM [ 19 ]. The use of the I-CAM-Q was originally limited; then, several surveys on the utilization of CAM were conducted using this questionnaire in several countries [ 20 30 ]. As the type and circumstances of CAM may vary greatly according to differences in the cultural backgrounds of each country, an adapted version of the I-CAM-Q may be developed before implementation in a survey [ 23 , 27 ].…”
Section: Introductionmentioning
confidence: 99%